LEADERSHIP DEVELOPMENT, EMPOWERING LEADERSHIP DAN PERAN JOB SATISFACTION SEBAGAI VARIABEL MEDIASI DALAM UPAYA MENINGKATKAN ORGANIZATIONAL COMMITMENT - Maria Valeria Roellyanti (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2016)
The study was aimed to examine the effect of Leadership Development and Empowering Leadership on the Organizational Commitment, that mediated by Job Satisfaction. Respodent of this study was taken from employees of Disperindagkop of Sleman Regency. This study was conducted considering two factors of Leadership Development, i.e. coaching, training and development and four factors of Empowering Leadership, i.e. enhancing the meaningfulness of work, fostering participation in decision making, expressing confidence in high performance, providing autonomy from bureaucratic constraints. The Structural Equation Modeling (SEM) were used for developing theoretical and analyzing of this study.. Result of this study found that the two factors of Leadership evelopment and four factors of Empowering Leadership effected on Job Satisfaction, and than the correlation between Job Satisfaction and the organizational commitment was founded positive effect. Development policies and programs in Disperindagkop should therefore focus on building Leadership Development and Empowering Leadership to make the hight Job Satisfaction and hight organizational commitment of it’s employees. Keywords: Leadership Development, Empowering Leadership, Job Satisfaction, Organizational Commitment, Structural Equation Modeling.